Respuesta :
[tex]\bf (\stackrel{x_1}{6}~,~\stackrel{y_1}{5})\qquad (\stackrel{x_2}{-6}~,~\stackrel{y_2}{9}) ~\hfill \stackrel{slope}{m}\implies \cfrac{\stackrel{rise} {\stackrel{y_2}{9}-\stackrel{y1}{5}}}{\underset{run} {\underset{x_2}{-6}-\underset{x_1}{6}}}\implies \cfrac{4}{-12}\implies -\cfrac{1}{3}[/tex]
Answer:
[tex]\large\boxed{slope=-\dfrac{1}{3}}[/tex]
Step-by-step explanation:
The formula of a slope:
[tex]m=\dfrac{y_2-y_1}{x_2-x_1}[/tex]
(x₁, y₁), (x₂, y₂) - points on a line
We have the points
(6, 5) → x₁ = 6, y₁ = 5
(-6, 9) → x₂ = -6, y₂ = 9
Substitute:
[tex]m=\dfrac{9-5}{-6-6}=\dfrac{4}{-12}=-\dfrac{4:4}{12:4}=-\dfrac{1}{3}[/tex]